Strategic Integration of Cloud Cybersecurity for Resilient Digital Business Transformation - Erika, Erika; Hari Safariningsih, Ratna Tri; Cahyono, Dwi; Rangi, Noah (ADI Publisher, 2025)
The increasing reliance on cloud computing technologies has driven digital business transformation across various industries, offering scalability, flexibility, and cost efficiency. However, this rapid adoption has simultaneously introduced complex cybersecurity challenges, including data breaches, unauthorized access, and system vulnerabilities that threaten operational continuity and trust. In response to these growing concerns, this study aims to analyze and develop effective cloud based cybersecurity strategies that enhance the resilience of digital business operations during transformation processes. The objective of this research is to identify and evaluate strategic cybersecurity practices that can strengthen cloud infrastructure during digital change. Employing a mixed method approach, the research combines an extensive literature review with qualitative expert interviews involving IT professionals and cybersecurity practitioners from cloud reliant enterprises. A total of 126 participants were involved in the data collection phase, comprising 98 valid survey respondents and 28 interview informants. The results reveal that while many organizations have implemented basic cloud security protocols, only a few have adopted comprehensive, adaptive frameworks capable of withstanding evolving cyber threats. Key strategic elements identified include the integration of zero trust architecture, continuous risk assessment, multi factor authentication, cloud native security tools, and regular employee training. Furthermore, organizations that embedded cybersecurity planning into their digital transformation roadmap demonstrated higher resilience, faster recovery from incidents, and stronger regulatory compliance. Based on these findings, the conclusion emphasizes that a proactive, strategy driven approach to cloud cybersecurity not only mitigates risks but also strengthens the long term sustainability of digital transformation efforts. The proposed framework serves as a guide for decision makers seeking to secure their cloud infrastructure while maintaining agility and innovation in an increasingly digital and threat prone business environment.